Conducting educational research : guide to completing a major project - Boudah, Daniel J. (Thousand Oaks, California : SAGE Publications, 2011)
Designed to be used during the research process, Conducting Educational Research walks readers through each step of a research project or thesis, including developing a research question, performing a literature search, developing a research plan, collecting and analyzing data, drawing conclusions, and sharing the conclusions with others. Throughout the book, Daniel J. Boudah covers all types of research (including experimental, descriptive, qualitative, group designs, and single subject designs) and helps readers link research questions to designs, designs to data sources, and data sources to appropriate analyses.
Chapter 1. Research in Education Conducting Research in Education -- Chapter 2. Identifying a Research Problem, Question, and Searching Relevant Literature -- Chapter 3. Understanding Relevant Literature and Writing a Literature Review -- Chapter 4. Issues in Validity and Reliability -- Chapter 5. Designing and conducting experimental research -- Chapter 6. Designing and Conducting Qualitative Research -- Chapter 7. Designing and Conducting Descriptive Research -- Chapter 8. Creating a Research Proposal -- Chapter 9. Analyzing and Interpreting Experimental Research From Designing and Conducting, to Analyzing and Interpreting Experimental Research -- Chapter 10. Analyzing and Interpreting Qualitative Data -- Chapter 11. Analyzing and Interpreting Descriptive Research -- Chapter 12. Writing Research Reports
Includes index.
Keywords: EDUCATION RESEARCH